Azas Personalitas Keislaman dalam Kompilasi Hukum Islam - Zulkarnain Suleman (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
The core application of Islamic personality is not a separate entity relationships on the basis of legal relations. Perfection and absolute principle of Islamic personalities must be supported by elements of legal relationship under Islamic law. It needs various strategies to apply the principles of Islamic personality. There are two main strategies to implement the principles of Islamic personalities. That is what he calls a common guide and the guide during the legal relationship. The definition of common standards is a benchmark that is formal. While the definition of the benchmark when there is that in the event of a legal relationship both parties are equally Muslim and legal bond that ties them to do under Islamic law.